Pregnancy outcome in patients with fibroid - Maliwad, Antima Kirtikumar; Thaker, Rajal; Shah, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Fibroids are benign smooth muscle cell tumour of the uterus. In some patients of pregnancy associated with fibroid, it does not affect the outcome of pregnancy. On the other hand, various complications have been reported. Objective of current study was to assess the prevalence and obstetric complications of fibroid during pregnancy and it management. Methods: This was a prospective study. The study was conducted at tertiary care centre, obstertrics & gynecology department over a period of nine months September 2013 to May 2014. Total 17 pregnant patients with >3 cm fibroid were included in the study. They were followed during antenatal period. Maternal age, parity, size of fibroid, complications during pregnancy, labour, and delivery, mode of delivery and indications of cesarean section were noted. Results: Incidence of fibroid during pregnancy was 0.4%. Out of 17 patients, majority 9 (52.9%) were between 26-30 years of age group, majority 7 (41.1%) were diagnosed between 21-28 weeks and 14 (82.3%) were multigravidas. Normal vaginal delivery occurred in 3 (20%), while 12 (80%) delivered by cesarean section. There were 8 (47%) patients who had no complication whereas 9 (52.9%) had some complication. Pain was present in 7 (41.1%). PROM and preterm labour was present in 3 (17.6%) and 2 (11.7%) respectively. Abortion and IUD occurred in 2 (11.7%) and in 1 (5.8%) respectively. LBW and IUGR was present in 5 (29.4%) and 3 (17.6%) respectively. PPH was present in 6 (35.2%). Antenatal myomectomy performed in 1 (5.8%) and myomectomy at cesarean section performed in 2 (11.7%). Blood transfusion was given to 8 (47%) patients. Conclusions: Pregnant patients who have fibroids are to be carefully screened in the antenatal period, so as to have a regular follow up. The wide spread use of ultrasonography has facilitated diagnosis and management of fibroids in pregnancy. The site and size of fibroid is very important to predict its effect on the pregnancy. In selected patients, myomectomy during antenatal period and at cesarean section can give good results and better pregnancy outcome.